Prolonged postprocedural outbreak of Mycobacterium massiliense infections associated with ultrasound transmission gel. (April 2016) - Cheng, A.; Sheng, W.-H.; Huang, Y.-C.; Sun, H.-Y.; Tsai, Y.-T.; Chen, M.-L.; Liu, Y.-C.; Chuang, Y.-C.; Huang, S.-C.; Chang, C.-I.; Chang, L.-Y.; Huang, W.-C.; et al.
Abstract: Postprocedural infections by Mycobacterium abscessus complex are increasing worldwide, and the source and route of transmission are infrequently identified. Here the extension of a previous clustering of paediatric patients with surgical site infections due to a single strain of the subspecies M. massiliense is reported. The investigation was conducted at a 2200-bed teaching hospital in Taiwan and included microbial surveillance of the environment (water, air, equipment and supplies) and a case–control study. We performed molecular identification and typing of the isolates by a trilocus sequencing scheme, confirmed by multilocus sequencing typing and pulsed-field gel electrophoresis. We investigated 40 patients who developed postprocedure soft tissue or bloodstream infections by M. massiliense (TPE101) during a 3-year period. Thirty-eight patients were identified at hospital A, and one newborn and her mother were identified at hospital B (185 km from hospital A). A case–control study identified the association of invasive procedures (adjusted odds ratio, 9.13) and ultrasonography (adjusted odds ratio, 2.97) (both p <0.05) with acquiring the outbreak strain. Isolates from the cases and unopened bottles of ultrasound transmission gel were all of strain ST48 and indistinguishable or closely related by pulsed-field gel electrophoresis. After replacement of contaminated gel, no new cases were detected during 18 months' follow-up. This investigation identified the use of contaminated gel as the common source causing an outbreak on a larger scale than had been recognized. Our findings halted production by the manufacturer and prompted revision of hospital guidelines.